2022
DOI: 10.1002/chem.202202584
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Primary Amine Catalyzed α‐Arylation of Simple Ketones via Asymmetric Retro‐Claisen Cleavage

Abstract: Highly enantioselective α‐arylation of simple ketones has been achieved by chiral primary amine catalyzed asymmetric retro‐Claisen cleavage of β‐diketones. This mild organocatalytic strategy enables the construction of α‐aryl tertiary carbon stereocenters in good yields and excellent enantioselectivities (up to 98 % ee) with the para‐quinone monoimines as aryl sources. Furthermore, oxidative catalytic asymmetric α‐arylation has also been realized with free p‐aminophenols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 77 publications
0
5
0
1
Order By: Relevance
“…2019 年, 罗三中等 [36] [37] 或对苯醌单亚胺 [38] 的不 对称逆 Claisen 反应/质子化, 高效高选择性地合成了一 系列含 α-叔碳手性中心的酮类化合物. 72% yield, 94% ee 59% yield, 77% ee 90% yield, 91% ee 29% yield, 88% ee 68% yield, 87% ee 52% yield, 94% ee…”
Section: β-二酮的不对称逆 Claisen 反应/质子化unclassified
“…2019 年, 罗三中等 [36] [37] 或对苯醌单亚胺 [38] 的不 对称逆 Claisen 反应/质子化, 高效高选择性地合成了一 系列含 α-叔碳手性中心的酮类化合物. 72% yield, 94% ee 59% yield, 77% ee 90% yield, 91% ee 29% yield, 88% ee 68% yield, 87% ee 52% yield, 94% ee…”
Section: β-二酮的不对称逆 Claisen 反应/质子化unclassified
“…Accordingly, much effort has been focused on the preparation of α,α-disubstituted β-diketones from α-monosubstituted β-diketones to be used in asymmetric retro-Claisen reaction. Much to our surprise, a literature survey revealed that 7 which could finally undergo C−C bond cleavage to form the corresponding chiral α-arylated ketones (Scheme 1b, right). However, this method suffers from at least two drawbacks: (1) only pquinone monoimines, rather than 1,4-benzoquinones, were used as aryl sources, possibly restricted by chiral primary amine catalyst, and (2) the reported catalytic method was not efficient enough for diketone substrates bearing benzylic group (R 1 ); indeed, there only one case has been reported in the literature.…”
mentioning
confidence: 99%
“…The preparation of 3g could be carried out at 1 mmol scale, and similar good results were obtained. To our delight, by using electron-deficient olefin 6 as the starting material, a one-pot, The absolute configuration of 3zb was determined by comparing HPLC analysis and optical rotation with previously reported literature, 7 and the configurations of all other products 3 were assigned by analogy assuming a uniform reaction pathway. The relative configuration of 7 was established by comparison with a known compound (see the Supporting Information for details).…”
mentioning
confidence: 99%
See 2 more Smart Citations